A meta-analysis of the relation between therapeutic alliance and treatment outcome in eating disorders - Graves, Tiffany A.; Mander, Johannes (The international journal of eating disorders, 2017)
The therapeutic alliance has demonstrated an association with favorable psychotherapeutic outcomes in the treatment of eating disorders (EDs). However, questions remain about the inter-relationships between early alliance, early symptom improvement, and treatment outcome. We conducted a meta-analysis on the relations among these constructs, and possible moderators of these relations, in psychosocial treatments for EDs. Twenty studies met inclusion criteria and supplied sufficient supplementary data. Results revealed small-to-moderate effect sizes, βs = 0.13 to 0.22 (p < .05), indicating that early symptom improvement was related to subsequent alliance quality and that alliance ratings also were related to subsequent symptom reduction. The relationship between early alliance and treatment outcome was partially accounted for by early symptom improvement. With regard to moderators, early alliance showed weaker associations with outcome in therapies with a strong behavioral component relative to nonbehavioral therapies. However, alliance showed stronger relations to outcome for younger (vs. older) patients, over and above the variance shared with early symptom improvement. In sum, early symptom reduction enhances therapeutic alliance and treatment outcome in EDs, but early alliance may require specific attention for younger patients and for those receiving nonbehaviorally oriented treatments.
Gesehen am 07.06.2017